STATE SUPPORT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Olimzhanov Sanjarbek; Yuldashev K.M (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article describes the role of small businesses in the national economy and their state support.